The impact mechanism of human activities over climate suitability based on social network data: evidence from China - Ren, Yujie; Tang, Xiaolan; Guo, Naijing; Du, Mengge (Journal of Environmental Engineering and Landscape Management, 2022)
The impact mechanism of human activities on climate suitability is critical for understanding the human-environment nexus. In this study, social network data from Sina Weibo Platform was collected to quantitatively examined the relationship between the seven major types of human activities and climate suitability. The results indicated that the impacts of entertainment, tourism and daily life related human activities on climate suitability are significant (p-value < 0.05). With one-unit (one check-in record/km2) increase of entertainment and tourism related human activities, the coverage rate of climate suitable zone and the length of climate suitable period increase by 0.003% and 0.026 months, respectively. In contrast, one-unit of increase of daily life activities made the Theil entropy index of climate inequity and the length of climate suitable period increase 0.00035 units and shorten 0.014 months, respectively. Moreover, the impact mechanism of human activities on climate suitability showed a significant spatial heterogeneity within regions at different economic level or topographical conditions, which could be explained by the discrepancy of environmental policies, urban form and urban ventilation channel design strategies in China. This work exhibited a further step to new possibilities in clarifying the climate effect of human activities using open-sourced social network data.